Iso-material contour representation for process planning of heterogeneous object model. Issue 4 (7th April 2020) - Sharma, G K; Gurumoorthy, B
Abstract: Additive manufacturing is emerging as the preferred process for making heterogeneous objects. Planning the deposition of material is more complex for heterogeneous objects as the material variation has to be tracked along the path. This paper proposes an iso-material contour representation to generate the process plan for additive manufacturing given a smooth representation of heterogeneous object model. These contours represent the iso-material paths for deposition. As these paths shift along the direction of the gradation of material distribution, the deposition respects the gradient of the designed material distribution unlike iso-oriented paths generated by a raster scan method. Since the paths have the same material composition, material frequent change in the material composition is avoided, which, in turn, avoids the uneven deposition caused by the frequent start and stop of deposition while the material is being changed along the paths generated by the traditional raster scan. Associativity between the contours and the corresponding designed material feature is maintained, and therefore, changes in material composition are automatically propagated to the process plan. Graphical Abstract: